Answer:
simplify -1-18
Step-by-step explanation:
Subtract 18 from −1
−
19
the average rate of change is just the slope from (0,f(0)) to (1,f(1))
find f(0) and f(1)
![f(0)=-3(0)^4-(0)^3+3(0)^2+0+3=3](https://tex.z-dn.net/?f=f%280%29%3D-3%280%29%5E4-%280%29%5E3%2B3%280%29%5E2%2B0%2B3%3D3)
![f(1)=-3(1)^4-(1)^3+3(1)^2+1+3=-3-1+3+1+3=3](https://tex.z-dn.net/?f=f%281%29%3D-3%281%29%5E4-%281%29%5E3%2B3%281%29%5E2%2B1%2B3%3D-3-1%2B3%2B1%2B3%3D3)
slope from (0,3) to (1,3) is rise/run=(3-3)/(0-1)=0/-1
the average rate of change from x=0 to x=1 for f(x) is 0
Answer:
82
Step-by-step explanation:
Let the unknown number be x
If an unknown number is added to 8, this is expressed as;
8 + x
<em>If The sum is then divided by 9 to give the answer 10, then;</em>
<em>(8+x)/9 = 10</em>
<em>Cross multiply</em>
<em>8 + x = 9 * 10</em>
<em>8 + x = 90</em>
<em>x = 90 - 8</em>
<em>x = 82</em>
Hence the unknown number is 82
Answer:
should be 6cm
Step-by-step explanation:
if you are looking at a cube